2021
DOI: 10.3390/coatings11040402
|View full text |Cite
|
Sign up to set email alerts
|

Interface Characteristics and Anticorrosion Performances of Cold Galvanizing Coatings Incorporated with γ-chloropropyl Triethoxysilane on Hot-Dip Galvanized Steel

Abstract: The cold galvanizing coatings (CGCs) are used to repair old hot-dip galvanized steel (HDG) in numerous anticorrosion engineering, but poor adhesion of the CGC restricts its large-scale applications in the industries. For the purpose of overcoming the weak adhesion problems of the CGC on HDG, γ-chloropropyl triethoxysilane (CPTES) was added directly into cold galvanizing coatings (CPTES/CGC). Interface characteristics and related corrosion protection behaviors were investigated by the pull-off adhesion test, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In the present study, the thickness of the Zn coating deposited by the different processes was 100 µm ( Table 2 ). Thus, it required a minimum of 1 d for the solution to penetrate into the coating, whereas Li et al [ 36 ] observed that the penetration of the solution into an 80 µm cold galvanized coating on a steel substrate required 5 h. The present findings suggest that even the coating with the most severe defects, namely the arc thermal sprayed Zn coating, required a minimum of 1 d for the penetration of the solution to cause the oxygen-reduction reaction. The tendency for the dissolution of the Zn coating deposited by the plasma arc thermal spray process is identical to that observed in the arc thermal spray process, but the magnitude of the complex-plane impedance was greater ( Figure 7 b) than that of the latter after 1 h of exposure.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…In the present study, the thickness of the Zn coating deposited by the different processes was 100 µm ( Table 2 ). Thus, it required a minimum of 1 d for the solution to penetrate into the coating, whereas Li et al [ 36 ] observed that the penetration of the solution into an 80 µm cold galvanized coating on a steel substrate required 5 h. The present findings suggest that even the coating with the most severe defects, namely the arc thermal sprayed Zn coating, required a minimum of 1 d for the penetration of the solution to cause the oxygen-reduction reaction. The tendency for the dissolution of the Zn coating deposited by the plasma arc thermal spray process is identical to that observed in the arc thermal spray process, but the magnitude of the complex-plane impedance was greater ( Figure 7 b) than that of the latter after 1 h of exposure.…”
Section: Resultsmentioning
confidence: 53%
“…Thus, a broad capacitive loop was seen in the high to middle frequency at approximately −50° in the plasma arc thermal sprayed coatings, whereas the arc thermal sprayed coating exhibited a capacitive loop at −43°, as shown in Figure 8 c. When the period of exposure was extended, the active Zn particles initially reacted with the solution and deposited the corrosion products, namely ZnO/Zn(OH) 2 , Zn 5 (OH) 8 Cl 2 H 2 O (simonkolleite) and Zn 5 (OH) 6 (CO 3 ) 2 (hydrozincite), onto the surface, which acted as capacitors [ 37 ]. Therefore, the total impedance of the Zn coating of the different processes increased after 13 d of exposure as compared to earlier periods, as shown in Figure 7 c. The increase in the total impedance was caused because the active area of the Zn coating was reduced, which weakened the electrical connection between the particles and the steel substrate [ 36 ]. The corrosion products actively blocked the defects of the coating and resisted the diffusion of the solution [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kania et al [ 6 ] reported the negative influence of Bi added to a Zn bath on the corrosion resistance due to the presence of Bi precipitates. Li et al [ 7 ] remarkably improved the adhesion of Zn coating after the cold galvanizing by the use of γ-chloropropyl triethoxysilane. Cetinkaya et al [ 8 ] reported the impact of chemical treatment on Zn-Al-Mg coating produced by a hot-dip process in order to increase Zn fraction at the coating surface.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc metal has several characteristics that make it a well-suited corrosion protective coating for iron and steel products [ 1 , 2 ]. Its high corrosion resistance in different environment conditions accounts for its successful use as a protective coating on a variety of products and in many exposure conditions, especially in automotive and building applications [ 3 , 4 , 5 ]. In the automotive industry, hot-dip galvanized sheets, with 100% of zinc, or GALFAN (with 95% Zinc and 5% Al) are the most used products [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%